Poverty and health among CDC plantation labourers in Cameroon: Perceptions, challenges and coping strategies. - Valerie Makoge; Lenneke Vaandrager; Harro Maat; Maria Koelen (Public Library of Science (PLoS), 2017)
Creating better access to good quality healthcare for the poor is a major challenge to development. In this study, we examined inter-linkages between poverty and disease, referred to as poverty-related diseases (PRDs), by investigating how Cameroon Development Corporation (CDC) camp dwellers respond to diseases that adversely affect their health and wellbeing. Living in plantation camps is associated with poverty, overcrowding, poor sanitation and the rapid spread of diseases. In a survey of 237 CDC camp dwellers in Cameroon, we used the health belief model to understand the drivers (perceived threats, benefits and cues for treatment seeking) of reported responses. Using logistic regression analysis, we looked for trends in people's response to malaria. We calculated the odds ratio of factors shown to have an influence on people's health, such as food, water, sanitation challenges and seeking formal healthcare for malaria. Malaria (40.3%), cholera (20.8%) and diarrhoea (17.7%) were the major PRDs perceived by camp dwellers. We found a strong link between what respondents perceived as PRDS and hygiene conditions. Poverty for our respondents was more about living in poor hygiene conditions than lack of money. Respondents perceived health challenges as stemming from their immediate living environment. Moreover, people employed self-medication and other informal health practices to seek healthcare. Interestingly, even though respondents reported using formal healthcare services as a general response to illness (84%), almost 90% stated that, in the case of malaria, they would use informal healthcare services. Our study recommends that efforts to curb the devastating effects of PRDs should have a strong focus on perceptions (i.e. include diseases that people living in conditions of poverty perceive as PRDs) and on hygiene practices, emphasising how they can be improved. By providing insights into the inter-linkages between poverty and disease, our study offers relevant guidance for potentially successful health promotion interventions.